Analysis of Dermatologic Events in Vemurafenib-Treated Patients With Melanoma - Lacouture, Mario E. (AlphaMed Press, 2013)
BACKGROUND. Vemurafenib has been approved for the treatment of patients with advanced BRAF(V600E)-mutant melanoma. This report by the Vemurafenib Dermatology Working Group presents the characteristics of dermatologic adverse events (AEs) that occur in vemurafenib-treated patients, including cutaneous squamous cell carcinoma (cuSCC). METHODS. Dermatologic AEs were assessed from three ongoing trials of BRAF(V600E) mutation-positive advanced melanoma. Histologic central review and genetic characterization were completed for a subset of cuSCC lesions. RESULTS. A total of 520 patients received vemurafenib. The most commonly reported AEs were dermatologic AEs, occurring in 92%–95% of patients. Rash was the most common AE (64%–75% of patients), and the most common types were rash not otherwise specified, erythema, maculopapular rash, and folliculitis. Rash development did not appear to correlate with tumor response. Photosensitivity occurred in 35%–63% of patients, and palmar-plantar erythrodysesthesia (PPE) occurred in 8%–10% of patients. The severity of rash, photosensitivity, and PPE were mainly grade 1 or 2. In all, 19%–26% of patients developed cuSCC, mostly keratoacanthomas (KAs). The majority of patients with cuSCC continued therapy without dose reduction after resection. Genetic analysis of 29 cuSCC/KA samples demonstrated HRAS mutations in 41%. CONCLUSIONS. Dermatologic AEs associated with vemurafenib treatment in patients with melanoma were generally manageable with supportive care measures. Dose interruptions and/or reductions were required in <10% of patients.